Immune Checkpoint Inhibitors Combined With Chemotherapy Compared With Chemotherapy Alone for Triple-Negative Breast Cancer: A Systematic Review and Meta-Analysis - Ji, Qiao; Ding, Jingxian; Hao, Meiqi; Luo, Nachuan; Huang, Jiabing; Zhang, Wenxiong (Frontiers in Oncology, 2021)
Background It is still controversial whether immune checkpoint inhibitors (ICIs) can improve the curative effect when added to original standard chemotherapy treatment for triple-negative breast cancer (TNBC). We compared their antitumor efficacy and adverse effects (AEs) to make a better clinical decision. Methods Seven databases were searched for eligible articles. Progression-free survival (PFS), overall survival (OS), and AEs were measured as the primary outcomes. Results Nine randomized controlled trials (RCTs) involving 4,501 patients were included. ICI+chemotherapy treatment achieved better PFS (hazard ratio [HR]: 0.78, [0.70–0.86], p < 0.00001), OS (HR: 0.86, [0.74–0.99], p = 0.04), and complete response (584/1,106 vs. 341/825, risk ratio [RR]: 1.38, [1.01–1.89], p = 0.04). With the prolongation of survival, the survival advantage of ICI+chemotherapy increased compared with chemotherapy. Subgroup analysis suggested that the addition of ICIs might not have a better effect in Asian patients, patients with locally advanced disease, or patients with brain metastases. In the toxicity analysis, more Grade 3–5 AEs and serious AEs were found in the ICI+chemotherapy group. For Grade 3–5 AEs, more cases of diarrhea, severe skin reactions, pneumonitis, hepatitis, and adrenal insufficiency were related to the ICI+chemotherapy group. Conclusions ICI+chemotherapy appears to be better than chemotherapy alone for TNBC treatment, with better OS and PFS. However, its high rates of serious AEs need to be taken seriously. Systematic Review Registration PROSPERO Registration: CRD42021276394.